Analysis of differences in viscosity of coconut milk and milk - Nur Setiawati Rahayu; Ahmad Sulaeman; Budi Setiawan; Mukhlidah Hanun Siregar (Arsip Keilmuan Gizi (AKG), 2025)
A viscosity or viscosity test is a measurement method to see a liquid product's viscosity level. In the process of making food products, liquids are used as additional ingredients to bind other ingredients or as a way to cook food. The viscosity level of the liquid used during the cooking process or when making the product affects the quality of the product. Recently, there have been many modification processes in food and cooking techniques, starting from modifying the use of liquids such as replacing coconut milk with milk, or vice versa. Therefore, researchers are interested in studying whether these two materials can replace each other in terms of their viscosity. This research was carried out in the IPB University food experiment laboratory using laboratory experimental methods, and viscosity testing using a Brookfield brand viscometer with spindle no. 1 and a speed of 100 rpm. The test results will be analyzed using a paired t-test to see whether there are differences between each sample. Based on the analysis, it was found that skim milk (F2) was not significantly different from coconut milk F7 (400g grated coconut: 800ml water). So it can be concluded that coconut milk F7 can be replaced by milk F2 in terms of viscosity.